PEMBELAJARAN TERDEFERENSIASI PADA FASE PONDASI DI TK TUNAS RIMBA TANJUNG SELOR KALIMANTA UTARA - Ilham, Muhammad; Irmayani, Naim (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2024)
This research is based on attention to the management of learning in schools, especially the implementation of the independent curriculum at all levels of education. This research uses descriptive qualitative methods. Using data collection with observation, interview and documentation techniques. Based on the results of research in the form of interviews and direct observations of students' learning processes without using differentiated learning and using differentiated learning, it was found that this strategy was successful in increasing students' learning motivation at school. This was evident from the students who previously only silently observed when the teacher was explaining, began to actively ask questions and were enthusiastic about participating in the learning process in the classroom. Based on these findings, teachers need to have the skills to implement differentiated learning according to students' needs, create a pleasant learning atmosphere that is able to attract students' interest and focus, and of course design a more attractive room.